2014
DOI: 10.1002/nbm.3132
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic contrast‐enhanced MRI texture analysis for pretreatment prediction of clinical and pathological response to neoadjuvant chemotherapy in patients with locally advanced breast cancer

Abstract: The aim of this study was to investigate the potential of texture analysis, applied to dynamic contrast-enhanced MRI (DCE-MRI), to predict the clinical and pathological response to neoadjuvant chemotherapy (NAC) in patients with locally advanced breast cancer (LABC) before NAC is started. Fifty-eight patients with LABC were classified on the basis of their clinical response according to the Response Evaluation Criteria in Solid Tumors (RECIST) guidelines after four cycles of NAC, and according to their patholo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
102
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 113 publications
(109 citation statements)
references
References 38 publications
3
102
0
Order By: Relevance
“…Other modalities have relied on similar mean-value and texture analyses including ultrasound spectroscopy, diffuse optical spectroscopy and MRI methods for therapy response monitoring43444546. In patients with triple negative disease pre-treatment, MRI-based kinetic maps have demonstrated positive results for chemotherapy response prediction in “triple-negative” breast tumours.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other modalities have relied on similar mean-value and texture analyses including ultrasound spectroscopy, diffuse optical spectroscopy and MRI methods for therapy response monitoring43444546. In patients with triple negative disease pre-treatment, MRI-based kinetic maps have demonstrated positive results for chemotherapy response prediction in “triple-negative” breast tumours.…”
Section: Discussionmentioning
confidence: 99%
“…Results also strongly suggest that pre-treatment tumour heterogeneity can influence drug efficacy44. Texture analyses of dynamic contrast-enhanced MRI images have also been used4546 to predict neoadjuvant chemotherapy response. Specifically, results have indicated significant differences in GLCM-texture features between chemotherapy responding and non-responders patients from pre-treatment data46.…”
Section: Discussionmentioning
confidence: 99%
“…In comparison to other studies, texture analysis of MRI (Ahmed et al , 2013; Golden et al , 2013; Teruel et al , 2014), ultrasound spectroscopy (Sadeghi-Naini et al , 2014), and DOS (Sadeghi-Naini et al , 2015) images have been used to assess and monitor chemotherapy response in breast tumours during the course of treatment. Textural analysis of pretreatment MRI-based kinetic maps have indicated positive results for predicting chemotherapy response in ‘triple-negative’ breast tumours (Golden et al , 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Those results also strongly suggest that pretreatment tumour heterogeneity can influence drug resistance (Golden et al , 2013). Other similar studies have examined texture features of dynamic contrast-enhanced MRI images to predict NAC response (Ahmed et al , 2013; Teruel et al , 2014). Results have indicated significant differences in GLCM texture features between responders and non-responders at pretreatment (Ahmed et al , 2013) and have reported an increase in textural heterogeneity caused by necrotic tumour areas (Ahmed et al , 2013).…”
Section: Discussionmentioning
confidence: 99%
“…While Kuo et al 28 were the first to explore specific hepatocellular carcinoma imaging phenotypes that correlated with doxorubicin drug response in 2007 (28), more recently, a study in women who completed treatment for locally advanced breast cancer suggested that texture analysis of DCE MRI can enable us to predict response to neoadjuvant chemotherapy before its initiation (29). Understanding the spatial and temporal phenotypic, physiological, and genetic heterogeneity of most solid tumours has led to the realisation that most chemotherapy responses are not durable and that targeted therapies are necessary to improve outcomes (6, 30).…”
Section: Potential Value Of Radiomics and Radiogenomicsmentioning
confidence: 99%